2012
DOI: 10.1111/j.1752-8062.2011.00366.x
|View full text |Cite
|
Sign up to set email alerts
|

Deriving Competencies for Mentors of Clinical and Translational Scholars

Abstract: Although the importance of research mentorship has been well established, the role of mentors of junior clinical and translational science investigators is not clearly defined. The authors attempt to derive a list of actionable competencies for mentors from a series of complementary methods. We examined focus groups, the literature, competencies derived for clinical and translational scholars, mentor training curricula, mentor evaluation forms and finally conducted an expert panel process in order to compose t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
80
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(81 citation statements)
references
References 23 publications
1
80
0
Order By: Relevance
“…There are only two research studies that identify exactly which qualities make a good mentor [25,26]. Straus et al conducted interviews with faculty members from the University of Toronto Faculty of Medicine and the University of California, San Francisco (UCSF), School of Medicine about characteristics of successful and failed mentoring relationships [25].…”
Section: Qualities Of a Good Mentormentioning
confidence: 99%
See 3 more Smart Citations
“…There are only two research studies that identify exactly which qualities make a good mentor [25,26]. Straus et al conducted interviews with faculty members from the University of Toronto Faculty of Medicine and the University of California, San Francisco (UCSF), School of Medicine about characteristics of successful and failed mentoring relationships [25].…”
Section: Qualities Of a Good Mentormentioning
confidence: 99%
“…The authors found that successful mentoring relationships displayed reciprocity, mutual respect, clear expectations, personal connection and shared values. Abedin et al, using focus groups, as well as reviewing literature, mentor training curricula and mentor evaluations, derived a list of competencies expected of mentors of clinical and translational scholars [26]. These competencies can be divided into six themes: 1) communication and relationship management; 2) psychosocial support; 3) career and professional development; 4) advocacy and maintenance of scientific integrity; 5) research opportunity development; and, 6) clinical and translational investigator development [26].…”
Section: Qualities Of a Good Mentormentioning
confidence: 99%
See 2 more Smart Citations
“…A core competency approach similar to those defined by the ACGME should be encouraged for self-assessment. 9 Mentors are a valuable, but limited, resource. A mentor should recognize that mentoring represents a significant time commitment.…”
mentioning
confidence: 99%